놀이치료자의 발달수준과 치료적 동맹의 관계에서 역전이 관리능력과 심리적 소진의 매개효과 - 최언지; Choi Eon-ji; 이영애; Lee Young-ae (한국놀이치료학회지(놀이치료연구), 2020)
본 연구에서는 놀이치료자의 발달수준과 치료적 동맹의 관계에서 역전이 관리능력과 심리적 소진의 매개효과를 규명하였다. 연구의 대상은 서울 및 경기 지역에 소재한 아동 전문 상담기관, 복지관 내 놀이치료실, 병원 내 놀이치료실, 대학부설 놀이치료실 등에서 근무 중인 놀이치료자 278명 이었다. 수집된 자료는 SPSS 23.0과 AMOS 23.0 프로그램을 사용하여 분석하였으며 구조방정식 모형을 통해 모형의 적합도 및 변인들의 영향을 검증하였다. 본 연구에서 밝혀진 결과를 요약하면 다음과 같다. 첫째, 놀이치료자의 발달수준과 치료적 동맹 간의 관계에서 역전이 관리능력과 심리적 소진의 매개효과를 검증한 결과, 역전이 관리능력의 부분매개 효과가 유의하였으며, 심리적 소진의 매개효과는 유의하지 않은 것으로 나타났다. 둘째, 놀이치료자의 발달수준과 치료적 동맹 간의 관계에서 역전이 관리능력과 심리적 소진의 순차적 부분매개효과가 검증되었다. 이를 통해 놀이치료자의 치료적 동맹 향상을 위해 발달수준을 증진시키는 것뿐만 아니라 역전이 관리능력을 향상시키고 심리적 소진을 감소시키는 것이 중요한 요소임을 확인하였다. The purpose of this study is to verify the mediating effects of the countertransference management abilities and psychological burnout on the relationship between development level and the therapeutic alliance of play therapists. 278 play therapists working at child counseling centers and play therapy rooms in welfare centers, hospitals and universities around Seoul and Gyeonggi-do were selected as the subjects of this study. The collected data were analyzed by means of structural equation modelling. For the purposes of data analysis, the SPSS 23.0 program and AMOS 23.0 program were used. The main research findings are as follows. Firstly, in terms of the relationship between the play therapists’ developmental level and therapeutic alliance, countertransference management abilities show a partial mediating effect. On the other hand, psychological burn-out levels did not show a mediating effect between either developmental levels nor therapeutic alliance. Secondly, the effects of countertransference management abilities and psychological burn-out were partial mediating variables, and sequential mediating effect was also verified. As a result, this study shows a significance in play therapist’s countertransference management abilities and psychological burnout was revealed as an important variable, increasing therapeutic alliance in play therapy.